A force‐measuring device combined with ultrasound‐based elastography for assessment of the uterine cervix - Christine Rohr Thomsen; Maria Strandbo Schmidt Jensen; Anne Katrine Leonhard; Tanja Østerlund Mortensen; Pinar Bor; Puk Sandager; Mogens Hinge; Niels Uldbjerg (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction In this feasibility study, we hypothesize that the evaluation of cervical biomechanical strength can be improved if cervical length measurement is supplemented with quantitative elastography, which is a technique based on conventional ultrasound elastography combined with a force‐measuring device. Our aims were to: (a) develop a force‐measuring device; (b) introduce a cervical elastography index (CEI) and a cervical strength index (CSI; defined as cervical length × CEI); (c) evaluate how these indexes assess the cervical softening that takes place during normal pregnancy; and (d) how these indexes predict the cervical dilatation time from 4 to 10 cm. Material and methods An electronic force‐measuring device was mounted on the handle of the transvaginal probe, allowing for force measurement when conducting elastography. The study group concerned with normal cervical softening included 44 unselected pregnant women. Outcomes were CEI and CSI at different gestational ages. The study group for labor induction included 26 singleton term pregnant women admitted for labor induction. Outcome was defined as cervical dilatation time from 4 to 10 cm. Elastography measured the changes in mean gray value (intensity) during manual compressions. Region of interest was set within the anterior cervical lip. Results We found that the mean of all variables regarding cervical softening decreased from early to late pregnancy: ie cervical length from 34 to 29 mm, CEI from 0.17 to 0.11 N, and CSI from 5.9 to 3.1 N mm. Moreover, the cervical dilatation time during labor induction was associated with CEI, although not statistically significantly (area under the ROC curve of 0.67), but not with the Bishop score, the cervical length, or the CSI. Conclusions We propose that quantitative elastography based on changes in the intensity of the B‐mode ultrasound recording, in combination with a force‐measuring device on the handle of the vaginal probe, deserves further investigation as an approach for evaluation of cervical biomechanical strength.